2019
DOI: 10.1016/j.trf.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of dynamic merge control strategies on driving behavior on rural and urban expressways – A driving simulator study

Abstract: Harsh decelerations and abrupt lane changes of drivers on the outer expressway lane in response to merging platoon vehicles from on-ramps increase the crash-and congestion risk on expressways. Several merge control approaches are worldwide implemented. However, there is a gap in knowledge which driving behaviors determine whether a particular merge control approach is best for a rural or urban expressway. This study tests a number of dynamic merge control strategies, such as lane control signalization (eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…With respect to the mean maximum longitudinal deceleration, all types of drivers' mean maximum longitudinal deceleration decreased as the weaving length increased; however, no significant differences were found in mean maximum longitudinal deceleration between 100, 150 and 200 m of weaving length for the same type of drivers (F C (2,42) = 0.528, P = 0.593 > 0.05; F N (2,42) = 0.410, P = 0.666 > 0.05; F A (2,42) = 0.244, P = 0.784 > 0.05) or between different types of driver under the same weaving length (F 100 (2,42) = 0.117, P = 0.890 > 0.05; F 150 (2,42) = 0.493, P = 0.614 > 0.05; F 200 (2,42) = 0.362, P = 0.698 > 0.05). It seems that a longer weaving length might increase the risk of a crash, due to higher driving speed and deceleration (Reinolsmann, 2019;Ma,2020) [37,42]. This result is in agreement with a previous study by Yuan [23].…”
Section: Mean Speed and Mean Maximum Longitudinal Decelerationsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to the mean maximum longitudinal deceleration, all types of drivers' mean maximum longitudinal deceleration decreased as the weaving length increased; however, no significant differences were found in mean maximum longitudinal deceleration between 100, 150 and 200 m of weaving length for the same type of drivers (F C (2,42) = 0.528, P = 0.593 > 0.05; F N (2,42) = 0.410, P = 0.666 > 0.05; F A (2,42) = 0.244, P = 0.784 > 0.05) or between different types of driver under the same weaving length (F 100 (2,42) = 0.117, P = 0.890 > 0.05; F 150 (2,42) = 0.493, P = 0.614 > 0.05; F 200 (2,42) = 0.362, P = 0.698 > 0.05). It seems that a longer weaving length might increase the risk of a crash, due to higher driving speed and deceleration (Reinolsmann, 2019;Ma,2020) [37,42]. This result is in agreement with a previous study by Yuan [23].…”
Section: Mean Speed and Mean Maximum Longitudinal Decelerationsupporting
confidence: 91%
“…A set of driving behavior parameters was analyzed: mean speed (in km/h), mean longitudinal acceleration (s/m 2 ) and the standard deviation of lateral acceleration (m/s 2 ) (SD of lateral acceleration) (Ariën, 2013;Reinolsmann, 2019) [36,37]. Besides this, the lanechange position and lane-changing duration time were measured and analyzed (Toledo, 2007) [38].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…This evidence confirms that many drivers are reluctant to decelerate correctly. Other studies have shown that the terminal geometry (i.e., type, width, and length) affects the operational and safety performance of such facilities (6)(7)(8)(9). Calvi et al (6) demonstrated that the choice of designing a tapered or parallel lane significantly affects the speeds of diverging drivers, resulting in problematic forms of interaction with those drivers proceeding straight on the motorway.…”
mentioning
confidence: 99%
“…For analyzing drivers' stopping behavior, repeated measures analysis of variance ANOVA is often applied to analyze speed and acceleration differences between tested conditions (Ariën et al, 2013;Calvi, 2018;Charlton et al, 2018;Hussain et al, 2018;Reinolsmann et al, 2019). However, in this study it was not appropriate to conduct repeated measures ANOVA tests, as for different conditions some of the drivers stopped at the intersection while other passed.…”
Section: Data Collection and Analysismentioning
confidence: 99%